Micro- and nanopatterning using scanning electrochemical microscopy. - Mandler, Daniel. (Scanning Electrochem. Microsc. (2nd Ed.), 2013)
A review. The following topics are discussed: Patterning by the Direct and Feedback modes of the SECM (Semiconductor, metal, and inorg. material etching and deposition; deposition of conducting polymers; self-assembled monolayers, polymers, and biomol. patterning); Speed of patterning, resoln., and scope of materials and approaches. [on SciFinder(R)]
CAPLUS AN 2013:1282783(Conference; General Review)
Keywords: review micropatterning nanopatterning scanning electrochem microscopy